The Critical Period Hypothesis of Second Language Acquisition Theory of Eric Lenneberg's - Siahaan, Frisca (Pascasarjana Universitas HKBP Nommensen, 2022)
In second language acquisition, The Critical Period Hypothesis (CPH) holds that there is a critical time period for a person to learn a new language with native proficiency. This time usually begins around the age of two and ends just before puberty. According to the hypothesis, learning a new language after this critical period will be more difficult and unsuccessful. The crucial phase is the stage of a person's development when their nervous system is primed and sensitive to environmental stimuli, according to developmental psychology. If a person does not receive the appropriate environmental stimuli during this time, their capacity to learn new skills will deteriorate, compromising a variety of adult social functions. If a child does not learn a language during this vital era, they are unlikely to achieve native fluency in their first language. Because of the adaptability of the brain, a person is poised to learn new abilities throughout the critical period. Synapses, or brain connections, are extremely receptive to information. Some researchers refer to the'sensitive period' or weak critical period' as a synonym for the critical period. The sensitive phase is comparable to thecritical period in that it is characterized by a high level of neuroplasticity and rapid formation of new synapses in the brain. The key distinction is that the sensitive phase is thought to endure longer than puberty, but there are no hard bounds.